AB0428 The association between physical activity measured by actigraphy and fatigue in patient with rheumatoid arthritis. (23rd January 2014) - van Dartel, S.; Repping, H.; Knoop, H.; van Hoogmoed, D.; Bleijenberg, G.; van Riel, P.; Fransen, J.
Abstract : Background: Fatigue in rheumatoid arthritis (RA) could be related to several factors. 1 The disease process, as well as its consequences such as pain, mental health problems and activity limitations are contributed to fatigue in RA. 1 It is reasonable to assume that increased fatigue may limit physical activity, or vice versa that increased physical activity may reduce fatigue. However, so far as we know the association between daily physical activity level and fatigue in RA patients has not been studied before. Objectives: The objective of this study was to investigate whether there is an association between objectively measured physical activity and fatigue in RA patients. Methods: Consecutive RA patients of the rheumatology clinic of the Radboud University Nijmegen Medical Centre (N=152) were enrolled. Fatigue severity was measured using the fatigue severity subscale (CIS-fatigue) of the Checklist Individual Strength (CIS20), asking about fatigue the last two weeks. Physical activity was measured during 12 consecutive days with the actometer, an ankle worn motion sensing device that registers and quantifies physical activity. A general physical activity score (DOM) reflected the average physical activity over the total 12-day time period and was expressed in the average number of accelerations per 5-min period. The individuals' activity patterns were based on the 12 daily physical activity scores. Patients with at least 90% of the daily activity scores below the DOM were classified as pervasively passive. Patients with at least 90% of the daily scores above the DOM were classified as pervasively active while the remaining patients were labeled as fluctuating active. An one-way ANOVA with Scheffé's post-hoc test was performed to investigate whether there was a difference in fatigue between the three physical activity patterns. Linear regression analysis was performed with CIS-fatigue as dependent and DOM as independent variable with correction for confounders. Results: The mean (±SD) CIS-fatigue increased with activity pattern (p=0.020): in pervasively active patients it was 26.29 (11.81), in fluctuating active it was 31.49 (11.94) and in pervasively passive patients it was 35.50 (12.94). This difference between the pervasively active patients and pervasively passive patients was significant (p=0.022) but both the difference between the pervasively active and the fluctuating active patients (p=0.214) and pervasively passive and fluctuation active patients (p=0.227) was not significant. Lineair regression analysis confirmed that the relation between activity (DOM) and fatigue was significant (p=0.002) and non-linear, with correction for age and gender. Conclusions: In RA, a higher level of physical activity was associated with less fatigue. Pervasively active patients had a significantly lower CIS-fatigue score than the pervasively passive patients. So, increased fatigue may limit physical activity, or vice versa increased physical activity may reduce fatigue. References: Hewlett S, Chalder T, Choy E, et al. Fatigue in rheumatoid arthritis: time for a conceptual model. Rheumatology (Oxford, England) 2011;50:1004-1006. Disclosure of Interest: None Declared